Eksistensi Madrasah Diniyah Takmiliyah (Wustha, Ulya, dan Al Jami'ah) - Zulfahman Siregar; Rajab Rajab (Tarbiyatuna Kajian Pendidikan Islam, 2025)
The objective of this study is to examine the existence of Madrasah Diniyah Takmiliyah (MDT), particularly MDT Wustha, MDT Ulya, and MDT Al Jami’ah (Mandiri), which are worth maintaining as they are capable of shaping a generation that is faithful, devout, righteous, and of noble character. The identified issue is the current regulation that only covers MDT Ula (Elementary), while other levels of MDT, such as MDT Wustha, MDT Ulya, and MDT Al Jami’ah (Mandiri), lack clear regulations. This research employs a descriptive approach, with the research subjects consisting of principals, teachers, and students at Madrasah Diniyah Takmiliyah (MDT) in Padang City. The results of the study indicate that the existence of MDT, particularly MDT Wustha, MDT Ulya, and MDT Al Jami’ah (Mandiri), needs to be continuously maintained as they are capable of shaping a generation that is faithful, devout, righteous, and of noble character. Furthermore, the establishment of regulations for MDT Wustha, MDT Ulya, and MDT Al Jami’ah (Mandiri) is urgently needed to support the sustainability and development of MDT at all levels.